1988
DOI: 10.1210/endo-122-4-1639
|View full text |Cite
|
Sign up to set email alerts
|

Thein VitroSynthesis and Release of Proteins by the Human Oviduct*

Abstract: The purpose of this study was to identify major proteins synthesized by the human oviduct and to determine if the ability of the human oviduct to synthesize these proteins was correlated with a specific stage(s) of the menstrual cycle. Oviducts, obtained from normal menstrual and immediately postpartum women, were minced and cultured in the presence of labeled precursors. The culture medium was analyzed for newly synthesized proteins by electrophoresis, followed by fluorography. One-dimensional gel electrophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(62 citation statements)
references
References 30 publications
3
58
0
1
Order By: Relevance
“…Composed of two major domains, a catalytically inactive chitinase domain and a C-terminal O-glycosylation domain, OGP is expressed in response to estrogen stimulation in the oviduct of numerous mammals, including pig (Buhi et al, 1990), hamster (Robitaille et al, 1988), baboon (Boice et al, 1990), bovine , mice (Kapur and Johnson, 1985) and humans (Verhage et al, 1988). Co-incubation of OGP or media conditioned with OGP (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Composed of two major domains, a catalytically inactive chitinase domain and a C-terminal O-glycosylation domain, OGP is expressed in response to estrogen stimulation in the oviduct of numerous mammals, including pig (Buhi et al, 1990), hamster (Robitaille et al, 1988), baboon (Boice et al, 1990), bovine , mice (Kapur and Johnson, 1985) and humans (Verhage et al, 1988). Co-incubation of OGP or media conditioned with OGP (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Glycoproteins secreted by non-ciliated cells create an intraluminal environment able to immobilise spermatozoa (Hunter, 1995), to maintain the viability and fertilizing capability of spermatozoa (Pollard et al, 1991;Suarez et al, 1991;Chian et al, 1995) and to play a supportive role in sperm/egg interactions (Geng et al, 1997;Tulsiani et al, 1997). Differences in the production of oestrus-associated glycoproteins by oestrogen have been observed in the isthmus of baboon (Verhage and Fazleabas, 1988) and pig (Buhi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Oviductal fluid is a complex mixture of plasma-derived constituents plus proteins synthesized by the oviduct epithelium [25,28]. It has been reported that the oviduct can secrete many growth factors, such as epidermal growth factor (EGF), transforming growth factor (TGF), insulin-like growth factor (IGF), and activin [10,19,20].…”
mentioning
confidence: 99%